Ascorbic Acid Promotes Functional Restoration after Spinal Cord Injury Partly by Epigenetic Modulation - Jin Young Hong; Ganchimeg Davaa; Hyunjin Yoo; Kwonho Hong; Jung Keun Hyun (Cells, 2020)
Axonal regeneration after spinal cord injury (SCI) is difficult to achieve, and no fundamental treatment can be applied in clinical settings. DNA methylation has been suggested to play a role in regeneration capacity and neuronal growth after SCI by controlling the expression of regeneration-associated genes (RAGs). The aim of this study was to examine changes in neuronal DNA methylation status after SCI and to determine whether modulation of DNA methylation with ascorbic acid can enhance neuronal regeneration or functional restoration after SCI. Changes in epigenetic marks (5-hydroxymethylcytosine (5hmC) and 5-methylcytosine (5mC)); the expression of Ten-eleven translocation (Tet) family genes; and the expression of genes related to inflammation, regeneration, and degeneration in the brain motor cortex were determined following SCI. The 5hmC level within the brain was increased after SCI, especially in the acute and subacute stages, and the mRNA levels of Tet gene family members (Tet1, Tet2, and Tet3) were also increased. Administration of ascorbic acid (100 mg/kg) to SCI rats enhanced 5hmC levels; increased the expression of the Tet1, Tet2, and Tet3 genes within the brain motor cortex; promoted axonal sprouting within the lesion cavity of the spinal cord; and enhanced recovery of locomotor function until 12 weeks. In conclusion, we found that epigenetic status in the brain motor cortex is changed after SCI and that epigenetic modulation using ascorbic acid may contribute to functional recovery after SCI.